The factors that affecting the selective variables on the Malaysian stock market performance from 1988 to 2017 / Nurul Farhania Che Mohd Asri - Che Mohd Asri, Nurul Farhania (Faculty of Business and Management, 2019)
This research paper examines the factors that affecting the selective variables on the Malaysian stock market performance from 1988 to 2017. As for the 30 yearly data observations, this research applied time series analysis method with Ordinary Least Square (OLS) to determine the influence of selective variables towards stock market performance. The result indicates GDP shows the negatively insignificant relationship and money supply shows the positively insignificant relationship toward stock market performance. However, inflation shows positively significant result at 1% significant level, while exchange rate shows the negatively significant result at 1% significant level towards Malaysia stock market performance.